Movimentos Feministas: Um Estudo De Caso Sobre As Relações De Gênero Em Uma Universidade Pública - Ferreira, Fernanda Lourenzato [UNIFESP] (2017)
This research intends to investigate how gender relations occur at the Federal University of São Paulo (Unifesp) according to feminist movements and their vision at the university. For this research, post-critical methodologies in education were applied focusing on gender, postgender, post-feminism and queer studies through a methodological mosaic composed by documental researches about Unifesp, the restructuration and expansion of federal universities program (REUNI), an analysis of enrollment data and the REUNI impacts on the university; as well as semi-structured interviews with fourteen participants composed by a questionnaire that outlines a social-economic profile and inquires the female students about the gender relations and conflicts in all Unifesp campi. The research has developed in the following manner: it began with a bibliographic research presenting a brief historic on women’s history and feminism on occidental society, an introduction to feminist studies and the queer theory, and the relations between feminism and school education. Afterwards, REUNI, the Unifesp expansion from this program and a social-economic profile mapping of the students of Unifesp with an analysis of the impacts of REUNI at the university based off on female enrollments are exposed. Finally, under the point of view of conceptions, statements and reports of university’s feminist movement’s acts, analysis of the interviews were executed through field research guided by feminist and queer studies, emphasising the theorist Judith Butler and the concepts of gender binarism, heteronormativity, compulsory heterosexuality and deconstruction of identities. With this research, it is possible to conclude that the university’s expansion contributed to democratize the access and, therefore, to the arrival of feminist movements inside it. However, at the same time, violence and gender oppression emerged, needing to be incorporated by Unifesp as a challenge to be faced. For this reason, it is important that the university starts establishing partnerships with the feminist unions, creating environments of discussion, resistance and embracement, as well as reviewing the curricular contents of all majors in order to promote changes in gender relations on the university. Therefore, this research establishes itself of extremely importance for reviewing and creating new educational policies, not only on public universities but also on public and student assistance policies on all Brazilian universities.